Breeding Temperate Japonica Rice Varieties Adaptable to Tropical Regions: Progress and Prospects - Myrish Pacleb (MDPI AG, 2021)
Temperate japonica rice is mainly cultivated in temperate regions. Many temperate japonica varieties have a superior grain quality that is preferred in Northeast Asian countries such as Japan, Korea, and China. The changes in consumers’ preferences in Southeast Asia and Western countries has contributed to increasing the demand for temperate japonica. Most temperate japonica varieties developed in temperate regions typically exhibit extra-early flowering under the short-day conditions in the tropics, which usually results in severely reduced yields. Since 1992, we have been developing temperate japonica varieties that can adapt to tropical environments to meet the increasing demand for temperate japonica rice, having released six varieties in the Philippines. Especially, the yield of one of the temperate japonica varieties, Japonica 7, was comparable to the yields of leading indica varieties in the Philippines. Here, we discuss the current breeding initiatives and future plans for the development of tropical-region-bred temperate japonica rice.